Scope with respect to the dissumination between protecting creations in the fashion market as an industrial design or as part of copyright and its concrete situation in Peru - Bardales Mendoza, Enrique (2017)
In the present article, the author exposes the discussion that exists regarding the protection that products should have in the fashion field. To do this, it shows the various elements that exist in the field of intellectual property, with special emphasis on copyright and rights on industrial design.The problem is addressed taking into account the independence of criteria between the different forms of protection, the possible concurrence of rights on the same product and the particularities of the objects susceptible of protection in a medium subject to constant changes such as fashion. Likewise, a comparison is made with the legislative formulas that have been adopted in foreign countries.